Quality improvement programs and the professional nursing practice environment: an integrative review - Camila Hidemi Danno; Larissa Sapucaia Ferreira Esteves; Elena Bohomol
ABSTRACT Objectives: to analyze the knowledge produced regarding the practice environment in hospitals with quality improvement programs. Methods: integrative literature review performed in the Latin American and Caribbean Literature in Health Sciences databases, US National Library of Medicine/National Institutes of Health, Web of Science, Scopus and CINAHL, consisting in 10 articles. Results: data were presented and discussed using categories: Measures for the professional nursing practice environment; Hospital accreditation as an improvement program; Nursing autonomy, interpersonal relationship between nurse and doctor and the nurse as a manager and leader. Final Considerations: it was possible to analyze that the influence of quality improvement programs can be considered as favorable in the professional nursing practice environment. The survey also brings contributions to administration in implementing strategies aiming at continuous improvement in the environment characteristics.